Recent work at Freswick Links, Caithness, Northern Scotland - Batey, Collen E. (Hikuin, 1989)
Excavations at Freswick Links have been undertaken intermittently since the beginning of this century. However, only two excavators addressed themselves to the settlement of the Viking age on the site: A. O. Curie and V. G. Childe. The first recorded excavations were at Freswick Sands broch, in the northern part of the Links in the 1890s; these were undertaken by Sir Francis Tress-Barry of nearby Keiss Castle. This excavation was only one of a series of eight to be undertaken along the East Caithness coast by him during the period of only a few summers’ work. Although he characterised the broch tower and distinguished some extra-mural chambers, he made little mention of the later finds he recovered. These included, for example, Late Norse antler combs more typical of a 12th Century dating and found elsewhere on the Links.